Acceptance of Health Intervention Policies and Social Relations for Chronic Disease Sufferers - Adila Solida; Ardiyansyah Ardiyansyah; Ayu Nurkhayati (International Journal of Health and Social Behavior, 2025)
The prevalence of chronic diseases in Jambi City has tended to increase in the last three years, especially hypertension and diabetes mellitus. Chronic diseases that are high risk, high volume and high cost have an impact on the household economy of sufferers who tend to incur health costs that exceed the family's financial capacity (catastrophic). The existence of the Chronic Disease Management Program (Prolanis) from BPJS Health should contribute to reducing the number of chronic diseases, reducing the burden of disease and improving the social relations of chronic disease sufferers, however the coverage of Prolanis activity is still low and several responses from community experience indicate there are problems with the acceptability of the program. This research aims to measure the level of community acceptability of health interventions and social relations in the Prolanis practice as assessed by analyzing affective attitudes, burden, ethics, intervention coherence, costs, perceived effectiveness and self-confidence of chronic disease sufferers in Jambi City in 2023. The research was conducted with Quantitative research methods use a cross-sectional design. Respondents were selected based on a purposive sampling technique totaling 180 respondents spread across five Puskesmas work areas in Jambi City. The research instrument is a questionnaire. The research results show that the indicators of burden, ethics and effectiveness are the most dominant factors in influencing the acceptability of Prolanis participants. As a recommendation, it is suggested to the government and BPJS Health to increase public understanding of the importance of using Prolanis in an effort to reduce the number of chronic diseases in Jambi City.